KAP study sars among hospital workers in 4 publics hospitals in state of Selangor - Hasni H; Nor lzzah S; Sh. Ezat W.P. (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2005)
A self-administered questionnaire were sent to 4 public hospitals (HTAR, Tg. Karang, Banting, Kajang) in Selangor as a cross sectional study. They were subsequently distributed among hospital workers and ancillary staffs during the SARS outbreak in March 2003. The purpose of study was to measure knowledge, attitudes and practice (KAP) during the SARS outbreak. Response rate of 83.9% was achieved (118 out of 531). This KAP study approached according to 7 aspects i.e. general knowledge on SARS; perception on management of SARS outbreak; perception on the risk of contracting SARS; readiness to work handling SARS patients, compensation seen fit to hospital workers, overall universal precautions practiced and training received prior outbreak. Hospital workers were divided to 2 categories; direct possibility of being involved with SARS patients i.e. 47.4% (21 out of 148) and nondirectly involved i.e. 52.9% (237 out of 448). Majority of hospital workers are found to be non-directly involved with management of SARS patients. Hospital workers directly involved with SARS were found to have significant better knowledge on SARS (t= 3.907; p<0.005), perceived better managetnent on SARS by Ministy of Health (MOH) (X2=21.163 p;< 0.001) and perceived contracting the disease as higher (X2=32.07; p<0.001). However, they had lower readiness to work handling SARS cases (X2=2.25; p=1.33), but it was not significant. Community health nurses and ancillary staffs have the lowest level of knowledge on SARS Universal Precautions methods practiced more significantly among directly involved hospital workers were checking for body temperatures (p=0.039), wearing mask during examining patients (p=0.001), work according to policy and guidelines (p=0.023), wearing Personal Protective Equipments (PPE) such as gloves, goggles and shoes when examining patients (p=0.025) but since that there was supply lack of PPE